Perbedaan Hasil Belajar Penjumlahan Siswa Sekolah Dasar Melalui Problem Based Learning dan Contextual Teaching and Learning - Sholehati Sholehati; Khurin In Ratnasari (Program Studi Pendidikan Matematika, 2026)
The necessity to find learning models that are pertinent to elementary school pupils’ characteristics is what motivates this work. The main focus of this study is to compare the impact of the use of problem -based learning models and contextual learning on the learning outcomes of summation material for grade 2 students. This study employs a quantitative method The approach employed in this study was quantitative research using a quasi-experimental design with an unequal control design in which only post treatment measures are made. The sample consisted of 51 students from 2A and 2B. the 2A student group was given learning by applying problem-based learning strategies (PBL), while class 2B applied the contextual teaching and learning (CTL) model. Data is collected through observation, conversations, documentation, and the dissemination of the questionnaire. After that, the data collected through a questionnaire processed using the independent sample t-test aims to measure the significances of differences in student learning outcomes between the experimental group and the control group. At a significant level of 5%, the data analysis showed a significant difference between the two group, with significance value of 0,000 < 0,05. These findings indicate that contextual teaching and learning (CTL), which offers a more authentic and contextual teaching and learning experience, is more pertinent for students in the concrete operational level.